2022
DOI: 10.1136/bmjopen-2021-051569
|View full text |Cite
|
Sign up to set email alerts
|

Service use, clinical outcomes and user experience associated with urgent care services that use telephone-based digital triage: a systematic review

Abstract: ObjectiveTo evaluate service use, clinical outcomes and user experience related to telephone-based digital triage in urgent care.DesignSystematic review and narrative synthesis.Data sourcesMedline, Embase, CINAHL, Web of Science and Scopus were searched for literature published between 1 March 2000 and 1 April 2020.Eligibility criteria for selecting studiesStudies of any design investigating patterns of triage advice, wider service use, clinical outcomes and user experience relating to telephone based digital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…In contrast, medical telephone triage has been extensively evaluated during A systematic review analysing 13 observational studies and 10 studies that simulated high-risk patients, safe triage was found in 46% to 97% [26]. Another systematic review involving computer-assisted telephone triage in urgent care [27] pointed out four studies that indicated potential undertriage errors [28] [29] [30] [31]. Notably, hospitalisation rates of patients who were advised to seek non-urgent care ranged from 9.2% to 48%.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, medical telephone triage has been extensively evaluated during A systematic review analysing 13 observational studies and 10 studies that simulated high-risk patients, safe triage was found in 46% to 97% [26]. Another systematic review involving computer-assisted telephone triage in urgent care [27] pointed out four studies that indicated potential undertriage errors [28] [29] [30] [31]. Notably, hospitalisation rates of patients who were advised to seek non-urgent care ranged from 9.2% to 48%.…”
Section: Discussionmentioning
confidence: 99%
“…Triage service is a preliminary service in medical diagnosis [29], serving as the first point of contact for patients in healthcare. They are crucial for improving efficiency and precision of medical services.…”
Section: Challenges and Solutions For Online Triage Systemsmentioning
confidence: 99%
“… 2 , 6 , 7 However, research to support digital triage services reducing health service demand is equivocal; some studies have reported a reduction in service use, while others have found no change. 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…The health benefits of these online and telephone platforms are realised only if patients and users follow the advice given, and estimates of this vary across studies and by type of advice provided; 8 , 9 , 11 for example, among users of the Healthdirect helpline that were 45 years or older, compliance was 77.5% for self-care and 68.6% for ‘attend ED immediately’, while 7.0% of callers self-referred to the emergency department (ED) within 24 hours. 12 For NHS 111, users are compliant only about half the time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation